A study on the influence of the formulation factors on in vitro release of ketoprofen from sustained release tablets - Larisa Cimpoaie; Luca Liviu Rus; Rareș Iuliu Iovanov (Amaltea Medical Publishing House, 2021)
Objectives. The aim of this study was to investigate the influence of formulation factors on in vitro release of ketoprofen from sustained release inert matrix tablets. Materials and methods. Laboratory scale, Ketoprofen sustained release inert matrix tablets were manufactured using Kollidon® SR as matrix formator, by direct tableting of powder blends. The influence of the formulation factors (X1 - matrix formator excipient and X2 - diluent type) on in vitro release of ketoprofen from sustained release tablets was studied by using a full factorial 23 experimental plan. Outcomes. Pharmacotechnical characterization of manufactured laboratory scale batches was performed and all 12 batches fulfilled European Pharmacopeia requests. In vitro release showed a sustained release profile in all cases. Variance analysis (ANOVA) showed a good correlation between experimental conditions and answers. In vitro release testing was performed in phosphate buffer pH = 7.4. Percentage release was determined spectrophotometrically at 258 nm. A decrease in the rate of in vitro release was registered, up to 4 h and 6 h when lactose DC and mannitol DC were used as diluents, respectively. Isomalt DC has increased the rate of in vitro release up to 6 h. Conclusions. In vitro release data, corresponding to formulation N1 shoed a good fitting with Weitbull, KorshmeyerPeppas and Higuchi models while in vitro release data corresponding to formulation N8 presented a good fitting with Weitbull and Korsmeyer-Peppas. In case of formulations N1 and N8 a non-Fickian diffusion mechanism seems to be involved in drug release from the matrix tablets.